Productivity and socioeconomic sustainability of Bubalus bubalis in the western lowlands of Venezuela - Carlos Alberto Calles Navas; Verena Torres Cardenas (Revista Científica)
The productivity and socioeconomic sustainability of Bubalus bubalis was compared to that of Bos indicus (as a reference), using an econometric livestock simulator in the low-lands of Barinas, Venezuela. Located at 7° 59’ 57.57’’ north latitude and 68° 59’ 00.13’’ west longitude, and from there to a radius of 50 kilometers. The simulator, built with Microsoft Excel, used the methodology of formulation and evaluation of agricultural investment projects. Given the importance of making prospective evaluations as a way of demonstrating sustainability, it was corroborated the future behavior of the family’s assets every time through the projected balance sheet: it was inquire, using a “Focus Group” with 80 breeders, the following variables: Number of hectares; carrying capacity; milk production per day; milk/cheese conversion; animal unit; projected income; projected health costs, pasture maintenance costs, feed costs and projected financial costs; depreciation; interest rate; inflation; investments; mortality rate; calving percentage, among others. The central motivation of the study was to show breeder families a different alternative to traditional cattle farming, in which the study area displaces a lot of forestry due to the expansion of agricultural lands. In contrast, buffalo farming requires forests. However, to convince farmers to apply this type of livestock; it was necessary to demonstrate its greater profitability. Upon inputting random values, internal rates of return (IRR) were obtained for a ten-year projection horizon and, comparing both type of livestock herds: the bubaline herd was more productive, as shown by a higher IRR in the year 2022 (IRR=35%), than the cattle herd (IRR=10%) during the same period. After statistically processing those resulted with a positive sign, by comparing means through Student’s t-tests for independent samples, using the SPSS statistical package: it was verified that the annual positive IRR results obtained are statistically and probabilistically valid with bilateral significance levels p <0.05 and p < 0.01 of admissible errors respectively, indicating that there are significant differences between the means. It was concluded that, in the western lowlands of Venezuela, Bubalus bubalis is both productive and socioeconomically sustainable. The latter could be corroborated by using Linear Regression in the projected financial statements (Income Statement and Balance Sheet) measuring the evolution of the family patrimony, with the livestock family being the fundamental socioeconomic unit and its central object of study. In 2023, the projections of the present work have been verified through the statistics provided by the Agrifood Network of Venezuela.